Estudos sobre o «vermelhão» do algodoeiro (III) - Coury, T.; Ranzani, G.; Malavolta, E.; Brasil Sobrinho, M. O. C. do (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1952)
In several cotton crops areas of the State of S. Paulo it was observed, during the years of 1948, 1949, and 1951, the appearance of a purple color of the leaves; the color appears in the opening of the bolls and was correlated with a decrease of production. The opinions concerning the cause of such abnormality were very different and sometimes contradictory; certain investigators attributed the disease to insect attack, others to bad climatic conditions whereas others to a potassium deficiency now called "fome de potássio" (potash hunger); our ideas on the subject is another one. We think that the disease is caused by lack of a suitable supply of magnesium. This opinion is largely based on the syntomatology found in the literature. To study the problem, several experiments were carried out, namely: 1. pot experiments using soil collected in areas where the disorder had appeared; 2. pot experiments controlling the water supply; 3. sand culture experiments omitting either potassium or magnesium; 4. leaf analysis of plant matrial collected troughout the Piracicaba County; 5. plot experiments with the varieties Texas, Express, and I.A. 817 Campinas. The first four experiments were discussed elsewhere. To study the point 5 an experiment was carried out, with the following treatments : 1 - NPKCaMg (no K added) - Mg supplied as MgSO4 (a soluble form); 2 -NPKCa (no Mg added); 3 -NPKCaMg (complete) - Mg supplied as MgSO4; 4 - NPKCaMg (complete) - Mg supplied as dolomitic limestone (a slightly soluble form) as a rate 2.5 higher than in the treatment 1 and 3. Organic matter as cottonseed meal was applied in the proportion of 500 kg per hectare. The experimental design was randomized blocks with 4 replications and the results can be summarized as follows: 1 the I.A 817 variety was the most strongly affected by the physiological disorder, with severe decrease in yield; 2. the disease occurred more frequently in the minus magnesium treatment; 3. dolomitic limestone is so effective as magnesium sulfate in the control of the disease as well in the raising of the yield; 4. in the minus K treatment it was observed a marked occurrence of the typical symptoms of potassium deficiency (cotton rust); 5. magnesium was actually, in the experimental conditions the responsible for the purple color (vermelhão) of the cotton leaves.